MEMANTAPKAN UKHUWAH MENUJU MASYARAKAT MADANI - Asy'ari, M. (State Institute of Islamic Studies (IAIN) Palu, 2005)
In Islam, brotherhood plays a great role. Even, Islam orders its adherents to build up brotherhood. Therefore, Islam orders its adherents to avoid conflict among them. If two groups of Muslim fight each other, Islam orders the other group of Muslim to be mediator of the two disputing groups. It is the concept of Islam for building up harmonious life among people that can lead to the intended civil society.